The role of students with practical nursing diplomas in the process of undergraduate nursing education: A qualitative study - Reza Hosseinabadi; Shirin Hasanvand; Mohammad Almasian; Somayeh Mirzayee-Sharifi (Wolters Kluwer Medknow Publications, 2020)
Background: Awareness of the experiences of students and educators in the educational process plays an important role in facilitating and improving this process. This study aimed to explain and investigate the experiences of nursing educators and students about the presence of students with practical nursing diplomas in the process of undergraduate education. Materials and Methods: In this qualitative study conducted from 2016 to 2018, which adopted a content analysis approach, 24 nursing students and educators of Lorestan University of Medical Sciences were selected using the purposive sampling method and were interviewed in depth. The data were manually recorded and analyzed using the Graneheim and Lundman method. Results: The three main themes of "from contrast to alignment with professional competence," "peaceful coexistence in the educational process," and "reflection of the perceived reality of the clinical environment," along with six categories and 30 subcategories were extracted from the interviews. Conclusions: It seems that monitoring and managing undergraduate courses more thoroughly, as well as raising the awareness of educators about the positive and negative dimensions of the presence of nursing students with practical nursing diplomas in undergraduate nursing courses can make it possible to optimize and improve students' learning process.